Here comes the wallet phone [wireless credit card]. - Boyd, J.
This paper discusses NTT DoCoMo's latest offering, the wireless credit card. DoCoMo, Japan's largest cellphone system operator, is working with major travel and banking organizations to extend the reach of its e-wallet service. These wallet phones are equipped with a wireless smart card chip, called FeliCa, and can be used to make electronic purchases at stores or vending machines, act as boarding passes on certain domestic flights, and authorize entry through corporate security doors. A year after DoCoMo introduced the e-wallet, the company has shipped about 6 million of the handsets. The company is expected to ship about 15 million handsets by the end of 2006.
Keywords: DoCoMo; FeliCa smart chip; Sony Corporation; Cash-and-credit handset; Credit-payment services; E-wallet.; Prepaid wireless cash card; Wallet phone; Wireless smart card chip